E-HEALTH COMMUNICATION ON INSTAGRAM POSTS: CONTENTS ANALYSIS OF ALODOKTER - Heidy Arviani; Roziana Febrianita (Universitas Lambung Mangkurat, 2020)
E-health on Instagram is a new area of health communication study. Alodokter is the number one digital health company in Indonesia with more than 20 million active users every month. As a website-based health tec company and the fastest-growing application in Southeast Asia, Alodokter has an Instagram account (@alodokter_id) with 730 thousand followers. In this paper, the author proposes three formulations of the problem: (a) What type of message is delivered by the health account on Instagram? (b) What type of content gets the most response? (c) How did Alodokter create their Instagram content strategy? The methodology used is qualitative with content analysis techniques. The author analyzes and categorizes 69 Instagram posts (15 August 2019 - 15 September 2019) from Alodokter. From the selected sample, there were 8 categories of posting themes. Body, Fact & Myth, Nutrition, Reproduction & Pregnancy, Breastfeeding, Growth & Child Development, Health Tips, Q&A. The most-used posting theme is Reproduction & Pregnancy (n = 19). This theme also gets the most comments (136) and likes (3062) in each post. The post and comment section provides opportunities to integrate followers to engage more online and offline. The last finding related to the Alodokter content strategy has a content strategy by creating unique visualizations oriented to storytelling. Alodokter Instagram's account has its own characteristic, namely the use of blue. For users, Alodokter provides the space for openness and ease of communication between patients and doctors.